The Northern Ireland Public Access Defibrillation (NIPAD) study: effectiveness in urban and rural populations. Issue 12 (29th January 2008) - Moore, M J; Hamilton, A J; Cairns, K J; Marshall, A; Glover, B M; McCann, C J; Jordan, J; Kee, F; Adgey, A A J
Abstract : Objective: To assess the impact of mobile automated external defibrillators (AEDs) on out-of-hospital cardiac arrests (OHCAs) in urban and rural populations. Design: Prospective before and after intervention, population study. Setting: Urban and rural areas of 160 000 each. Patients, interventions and main outcome measures: In 2004–6 the demographics of OHCAs were assessed. In 2005–6 AEDs were deployed (29 urban, 53 rural): 335 urban first responders (FRs) and 493 rural FRs were trained in AED use and dispatched to OHCAs. Call-to-response interval (CRI), resuscitation and survival-to-discharge rates for OHCA were compared. Results: In 2004 there were 163 urban OHCAs and the emergency medical services (EMS) attended 158 (ventricular fibrillation (VF) 27/158 (17.1%)). In 2005–6 there were 226 OHCAs, EMS attended 216 (VF 30/216 (13.9%)). In 2005–6 FRs were paged to 128 OHCAs (56.6%), FRs attended 88/128 (68.8%): 18/128 (14.1%) reached before the EMS. The best combined FR/EMS mean (SD) CRI in 2005–6 (5 min 56 s (4)) was better than the EMS alone in 2004 (7 min (3); p = 0.002). Survival rate was 5.1% in 2004, 1.4% in 2005–6 (p = NS). In 2004 there were 131 rural OHCAs, EMS attended 121 (VF 19/121 (15.7%)). In 2005–6 there were 122 OHCAs, EMS attended 114 (VF 19/114 (16.7%)). In 2005–6 FRs were paged to 49 OHCAs, FRs attended 42/49 (85.7%): 23/49 (46.9%) reached before the EMS. The best combined FR/EMS mean (SD) CRI in 2005–6 (9 min 22 s (6)) was better than the EMS alone in 2004 (11 min 2 s (6); p = 0.018). Survival rate was 2.5% in 2004, 3.5% in 2005–6 (p = NS). Conclusions: Despite improvement in CRI there was no impact on survival (witnessed arrest 32.8%, VF 15.6%). Trial registration number: ISRCTN07286796.